AN ANALYSIS OF LANGUAGE STYLE USED BY THE MAIN CHARACTER IN “FREE GUY” MOVIE - Fajar Wirawan; Widi Syaftinentias; Silviana Masran; Nofi Yenti Eka Putri; Wasgigin Wiyan Drazit (Ensiklopedia Education Review, 2022)
The language style can be defined as the words people use when they are in certain conditions or places. People also use the language style depending on who the audience is and where they are speaking. The use of the right language style is needed to convey the message well. Students need to understand its use to live a social life in their environments. Many inappropriate language styles are still used, resulting in unclear information being conveyed. Students are expected to better understand and be able to use the language by learning the style that fits with their needs. The purpose of this study were to analyze the type of language style, to find out the dominant type of language style and to describe the factors that affect Guy in “Free Guy” movie to speak in a different style.In this study, the researcher used descriptive qualitative research design to collect the data. This research design was chosen because it was more suitable to describe the data. The researcher uses two instruments to collect the data. They are personal documentation and human instrument.  Personal documentation is used to collect the conversation that contains the data and human instrument uses to support research in completing the data. The researcher analyze language style that used by the main character in “Free Guy” movie by grouped  the data that has been collected according to the type of language and the researcher determines the most dominant type of language style. Then, the researcher determined the factors that influence the differences in the use of language styles. After the researcher analyses the conversations that contained 5 types of language style, the researcher found that there are four types of language style used by Guy in the movie: formal style, casual style, consultative style, and intimate style, while the frozen style was not found in the "Free Guy" movie. For more details as follows: formal style consisted 3 data, consultative style 12 data, casual style 5 data, and intimate style 15 data. Second, of the four types, the most dominant type was the intimate style, which consisted of 15 data. Third, the researcher found 4 factors that influence the differences in the use of language styles. They were the participants involved in the dialogue, the situation and place where the conversation takes place, the purpose of the conversation and the topic of the dialogue.